2017
DOI: 10.1177/0363546517721686
|View full text |Cite
|
Sign up to set email alerts
|

Rotator Cuff Calcific Tendinitis: Ultrasound-Guided Needling and Lavage Versus Subacromial Corticosteroids: Five-Year Outcomes of a Randomized Controlled Trial

Abstract: No more significant differences were found in the clinical and radiological outcomes between barbotage combined with a SAIC versus an isolated SAIC after 5 years of follow-up. Registration: NTR2282 (Dutch Trial Registry).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 36 publications
4
58
0
1
Order By: Relevance
“…Although it would have been ideal to have a control group to rule out that the outcome is because of the selflimiting history of RCCT, we believe that, for the purpose of identifying prognostic factors, a large prospective cohort study is of sufficient methodological quality. Finally, the follow-up term of this study was 1 year; this is comparable to other studies [16,17,24], but some long-term studies on RCCT show that a substantial part of patients still have persisting shoulder complaints in the long term [7,26]. More research is needed to gain insight in predictive factors for persisting shoulder complaints in the long term.…”
Section: Discussionsupporting
confidence: 76%
“…Although it would have been ideal to have a control group to rule out that the outcome is because of the selflimiting history of RCCT, we believe that, for the purpose of identifying prognostic factors, a large prospective cohort study is of sufficient methodological quality. Finally, the follow-up term of this study was 1 year; this is comparable to other studies [16,17,24], but some long-term studies on RCCT show that a substantial part of patients still have persisting shoulder complaints in the long term [7,26]. More research is needed to gain insight in predictive factors for persisting shoulder complaints in the long term.…”
Section: Discussionsupporting
confidence: 76%
“…From the nine potentially relevant articles identified through titles and abstract review, three RCTs met the eligibility criteria after full-text review,16 18–20 one including the original publication and a 5-year follow-up16 19 (figure 1). Characteristics of included studies are presented in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In every RCT, the population was composed of adults with chronic RC calcific tendinopathy of at least 316 19 to 6 months’ duration 18 20. RC calcific tendinopathy was confirmed by radiography and/or ultrasound.…”
Section: Resultsmentioning
confidence: 99%
“…Another review by Louwerens al. [39] indicated good to excellent clinical outcomes in high-energy ESWT and US-guided needling, but the side effects and posttreatment complications for each individual patient should be taken into account [17,21,24,25]. Cho et al [27] showed that at least 28% of the patients included in their study did not fully recover after nonoperative treatments, and surgical treatment may be needed for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…guided percutaneous lavage (UGPL) [21] have also yielded good results, but might lead to complications such as vagus nerve stimulation, pain [1,22] and even skin disinfection [23]. Many patients even experience pain and discomfort, followed by recurring symptoms of the involved shoulder [17,21,24,25], and some of them require surgery nally. Nevertheless, more than 25% of patients who are resistant to conservative treatment and patients with severe symptoms persisting for more than six months need to undergo surgery [26,27].…”
mentioning
confidence: 99%